Use of SIFCON as a sustainable material in reinforced concrete beams - Kumar, S. Sundar; Ramesh, G.; Bharatkumar, B. H.; Bhashya, V.; Krishnamoorthy, T. S. (Journal of Structural Engineering, 2025)
Sustainability is the capacity to endure. Sustainable development is a pattern of resource use that aims to meet human needs while preserving the environment so that these needs can be met not only in the present, but also for future generations. The term was used by the Brundtland Commission which coined what has become the most often-quoted definition of sustainable development. Hence sustainable built environment can be achieved by proper use of the limited resources available through good design and execution. One of the basic requirement for any structure be sustainable is that it should be durable, it should have the ability to function satisfactorily in changing conditions without any detrimental effect on itself and to the surrounding environment. Concrete needs special attention to protect it from the aggressive environment which leads to distress in the structures in the form of reinforcement corrosion, carbonation and other durability related problems. The weak tensile capacity of concrete causes it to crack in the service condition itself. Most of the design codes consider the concrete in the tension zone as a cracked. Structurally this cracked section though can function safely it is the environment that surrounds the structure which induces distress in the members resulting in reduction in life of the structure. SIFCON is a type of fibre concrete with very high percent of steel fibres, the high amount of steel fibre makes SIFCON stronger in tension, though not strong enough to replace the steel and not economical to replace concrete, it enhances the cracking load of the section considerably, enabling the section to remain un-cracked at service loads. In the present work the cracking load of a beam has been enhanced by replacing a portion of cross-section with SIFCON. Material properties of SIFCON have also been investigated.